Global and regional molecular epidemiology of HIV-1, 1990–2015: a systematic review, global survey, and trend analysis. Issue 2 (February 2019) - Hemelaar, Joris; Elangovan, Ramyiadarsini; Yun, Jason; Dickson-Tetteh, Leslie; Fleminger, Isabella; Kirtley, Shona; Williams, Brian; Gouws-Williams, Eleanor; Ghys, Peter D; ,
Summary: Background: Global genetic diversity of HIV-1 is a major challenge to the development of HIV vaccines. We aimed to estimate the regional and global distribution of HIV-1 subtypes and recombinants during 1990–2015. Methods: We searched PubMed, EMBASE (Ovid), CINAHL (Ebscohost), and Global Health (Ovid) for HIV-1 subtyping studies published between Jan 1, 1990, and Dec 31, 2015. We collected additional unpublished HIV-1 subtyping data through a global survey. We included prevalence studies with HIV-1 subtyping data collected during 1990–2015. We grouped countries into 14 regions and analysed data for four time periods (1990–99, 2000–04, 2005–09, and 2010–15). The distribution of HIV-1 subtypes, circulating recombinant forms (CRFs), and unique recombinant forms (URFs) in individual countries was weighted according to the UNAIDS estimates of the number of people living with HIV (PLHIV) in each country to generate regional and global estimates of HIV-1 diversity in each time period. The primary outcome was the number of samples designated as HIV-1 subtypes A, B, C, D, F, G, H, J, K, CRFs, and URFs. The systematic review is registered with PROSPERO, number CRD42017067164. Findings: This systematic review and global survey yielded 2203 datasets with 383 519 samples from 116 countries in 1990–2015. Globally, subtype C accounted for 46·6% (16 280 897/34 921 639 of PLHIV) of all HIV-1 infections in 2010–15. Subtype B was responsible for 12·1% (4 235 299/34 921 639) of infections, followed by subtype A (10·3%; 3 587 003/34 921 639), CRF02_AG (7·7%; 2 705 110/34 921 639), CRF01_AE (5·3%; 1 840 982/34 921 639), subtype G (4·6%; 1 591 276/34 921 639), and subtype D (2·7%; 926 255/34 921 639). Subtypes F, H, J, and K combined accounted for 0·9% (311 332/34 921 639) of infections. Other CRFs accounted for 3·7% (1 309 082/34 921 639), bringing the proportion of all CRFs to 16·7% (5 844 113/34 921 639). URFs constituted 6·1% (2 134 405/34 921 639), resulting in recombinants accounting for 22·8% (7 978 517/34 921 639) of all global HIV-1 infections. The distribution of HIV-1 subtypes and recombinants changed over time in countries, regions, and globally. At a global level during 2005–15, subtype B increased, subtypes A and D were stable, and subtypes C and G and CRF02_AG decreased. CRF01_AE, other CRFs, and URFs increased, leading to a consistent increase in the global proportion of recombinants over time. Interpretation: Global and regional HIV diversity is complex and evolving, and is a major challenge to HIV vaccine development. Surveillance of the global molecular epidemiology of HIV-1 remains crucial for the design, testing, and implementation of HIV vaccines. Funding: None.